Detection and qPCR quantification of seven Fusarium species associated with the root rot complex in field pea. Issue 2 (3rd April 2018) - Zitnick-Anderson, Kimberley; Simons, Kristin; Pasche, Julie S.
Abstract: Multiple plant pathogens cause root rot on field pea, including Aphanomyces euteiches, Rhizoctonia solani and numerous Fusarium spp. In North Dakota, root rot pathogens have been a contributing factor in the decline in area planted to field pea over the past decade. Real-time quantitative PCR (qPCR) has proven valuable in quantifying a multitude of host–pathogen interactions. However, no qPCR assays are available to effectively quantify Fusarium spp. associated with root rot in field pea. The objective of this study was to develop multiplex qPCR assays to quantify seven Fusarium spp. commonly associated with field pea ( F. acuminatum, F. avenaceum, F. culmorum, F. graminearum, F. redolens, F. solani and F. sporotrichioides ). Primers and associated hydrolysis probes designed for each Fusarium sp. were combined into three multiplexed assays. Assay amplification efficiencies ranged from 93 to 108 and the regression coefficient for all assays was greater than 0.97 on serial dilutions of pure fungal DNA. All three multiplex assays amplified down to 40 pg µL −1 Fusarium DNA. Multiplex qPCR assays proved sensitive and specific based on evaluations of pea plants inoculated under greenhouse conditions and plants displaying symptoms of root rot collected from commercial pea fields. Annealing temperatures and reaction components were the same for all assays, providing interchangeability and versatility in each multiplexed assay. These assays will aid researchers in advancing the information available for the Fusarium –host interactions for many important crop systems.